2012
DOI: 10.1039/c2em30119a
|View full text |Cite
|
Sign up to set email alerts
|

Different collector types for sampling deposition of polycyclic aromatic hydrocarbons – comparison of measurement results and their uncertainty

Abstract: Different collector types, sample workup procedures and analysis methods to measure the deposition of polycyclic aromatic hydrocarbons (PAH) were tested and compared. Whilst sample workup and analysis methods did not influence the results of PAH deposition measurements, using different collector types changed the measured deposition rates of PAH significantly. The results obtained with a funnel-bottle collector showed the highest deposition rates and a low measurement uncertainty. The deposition rates obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…34 Some of the comparison investigations were done with bulk deposition samplers, while others used wet-only samplers and estimates of uxes from snowpack accumulation. Both of these could underestimate total deposition, the wet-only samplers by excluding dry particle deposition [30][31][32]35 and snowpack accumulation by revolatilization losses over the season. [30][31][32] Specic discussions and comparisons for compound classes are done in the sections below.…”
Section: Resultsmentioning
confidence: 99%
“…34 Some of the comparison investigations were done with bulk deposition samplers, while others used wet-only samplers and estimates of uxes from snowpack accumulation. Both of these could underestimate total deposition, the wet-only samplers by excluding dry particle deposition [30][31][32]35 and snowpack accumulation by revolatilization losses over the season. [30][31][32] Specic discussions and comparisons for compound classes are done in the sections below.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison among different collector types, sampling workup procedures, and analysis methods showed that the highest deposition rates of PAHs and low measurement uncertainty were obtained with a funnel-bottle collector [24,133]. The deposition rates obtained with the wet-only collectors were the lowest at industrial sites and under dry weather conditions.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…The deposition rates obtained with the wet-only collectors were the lowest at industrial sites and under dry weather conditions. For the open-jar collectors, the measurement uncertainty was high [133]. Several monitoring campaigns were conducted in different types of sampling sites and in different seasons in order to measure PAHs deposition fluxes and to study the effect of the Meteoclimatic parameters on monitored levels (see Table 8).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Different studies were performed for investigating organic [8][9][10][11][12][13][14][15][16] and inorganic micropollutants [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] in atmospheric deposition using bulk deposition methods. The total depositions (bulk) are collected by passive exposure of a "bottle/cylindrical funnel" system with standardized dimensions, for weekly and/or monthly collecting period in annual monitoring studies.…”
Section: Introductionmentioning
confidence: 99%